Android-Based Mathematics Learning Media Development Research: A Bibliometric Analysis using VosViewer - Soebagyo, Joko; Maghfiroh, Lusiana Nur (Jurnal Pendidikan MIPA, 2022)
The purpose of this research is to determine the title and abstract about Development Of Android Mathematics in 2017-2022. The research data is taken from articles published online through Google Scholar with the keywords development of mathematics. Methods Data collection is done by checking and recording all data information about the number of articles, citations, and authors. The analysis used is full counting in the VOSViewer application. The total number of articles sampled in this study were 1000 articles with the technique of analyzing the image results obtained from the VOSviewer application, including Network visualization, Overlay visualization, and Density visualization. By using VosViewer researchers can visualize several analyzes of a research that researchers want to do Keywords: bibliometrics, mathematics development, development of android mathematics. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp842-852